Population Structure of Turbo setosus and Strombus labiatus Collected By Rads in The Intertidal Area of Serinting Beach Special Economic Zone (SEZ) Mandalika - Linda Lestari; Karnan; Imam Bachtiar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Harvesting gastropods and other intertidal biota during lowest tides called Madak, is a traditional activity of coastal community on the Lombok Island. The Madak tradition has the potential to be used as a biology learning resource in schools. Variations in the size of Gastropods can be used as a source of studying population ecology. The present study aimed to describe quantitatively Gastropoda populations harvested during the madak. This study was carried out by collecting snail Turbo setosus and Strombus labiatus shells harvested in the intertidal area of ​​Serinting Beach. Convenience sampling was applied to collect data from 5 people in 5 days. There were 120 individuals of T. setosus and 240 individuals of S. labiatus collected from 25 rads with varying shell sizes. The shell size of T. setosus ranges from 3.32 to 7.19 cm, which is then divided into 8 classes. The average size of the harvested shells was 5.08 cm with a standard deviation of 1.96 cm, which means that the distribution of the data obtained was less varied. The size of S. labiatus shells ranges from 2.40-4.78 cm which is then divided into 9 classes. The average size of harvested shells was 3.48cm with a standard deviation of 0.92 cm, which means that the distribution of the data obtained is less varied. The population structures of T. setosus and S. labiatus harvested were less diverse, so further research is needed to determine the population structure of T. setosus and S. labiatus found in nature.